A Size‐Flexible Organometallic Box for the Encapsulation of Fullerenes. (20th March 2019) - Martínez‐Agramunt, Victor; Eder, Tobias; Darmandeh, Heidar; Guisado‐Barrios, Gregorio; Peris, Eduardo
Abstract: A palladium‐cornered molecular square with four pyrene‐bis(imidazolylidene) bridging ligands is reported. This metallo‐polygon can encapsulate C60 and C70 . The X‐ray diffraction structures of the empty cage as well as the cages complexed with both fullerenes are described. The fullerene encapsulation produces perturbations in the structural parameters of the metallo‐square, showing that it can adjust the shape of its cavity to the size of each fullerene.